DIKOTOMI â€œDUNIA LAMAâ€ DAN DUNIA MODERNâ€ DALAM PANDANGAN TOKOH REMAJA DALAM NOVEL MANDY HUBBARD PRADA AND PREJUDICE - Ni Ketut Mirahayuni; Susie Chrismalia Garnida; Mateus Rudi Supsiadji (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. This article deals with the characteristics of young adult literature and explores the dichotomy of two worlds in Mandy Hubbard’s Prada and Prejudice. The focus of analysis is the experience of Callie Montgomery during her school tour to London. She is an American senior high school student of the 21st century. She is popular as a bookworm and clumsy girl in her social relation with her mates of her age. Callie’s mysterious experience in which she enters an English society 200 years back after falling down when she was trying her new shoes of Prada’s brand for a recognition of her mates forced her to face a life of two different worlds separated by 200 years. The old world is represented by a society’s life in England in 1815. The new world is represented by the character’s introspection of the 21st life. The analysis discusses three aspects of the two worlds: physical, social, and spiritual world. There is also a discussion on the main character’s critical attitudes and her understanding on the differences of the two worlds, particularly on her own personality. Key words: young adult literature, personal identity, modern and old worlds